IMPLIKASI KEPALA DAERAH DARI CALON PERSEORANGAN TERHADAP EFEKTIFITAS HUBUNGAN KERJA KEPALA DAERAH DENGAN DPRD - Anwar, Anwar (Jurnal Konstitusi, 2012)
The decision made by the Constitution Court in a case decision No. 5/PUU-V/2007 abbrogated the Article 56 and 59 of the 2004 Law No. 32 as a basis for allowing an individual candidate to participate in an election of  local heads. From the result of this research, it is found out that the existence of an individual candidates in a election of a local head is in line with the spirit of the 1945 Constitution namely giving an equal opportunity to every citizen to run the government since the condition of political parties that have not yet become conducive instruments to prepare candidates of leaders at all levels of state organization. If a local head is from an individual candidate, no substantial implication is on the effectiveness of the working relationship between  the local head and the Local Parliament in terms of making local regulation, deterining  local budget and  of the function of control of the local parliament. It is also the case of the head and vice head of Garut coming from individual candidates, there is no substantial implication on the effectiveness of working relationship  between the local head and the local parliament of Garut.